GROWTH AND SURVIVAL OF SEEDLINGS AND SAPLINGS IN THE LOGGED - OVER FOREST, KINTAP, SOUTH KALIMANTAN - Jafarsidik, Yusuf S. (Secretariat of Forestry Research and Development Agency, 2004)
A study on demography, Â growth Â and survival ofÂ seedlings and saplings was conducted Â in the Hutan Kintap Â concenssion,Â Â South Kalimantan,Â Â Indonesia. The aim of Â the study Â was to monitor Â pattern Â of growth of seedlings and saplings among different types of logged - Â over forest, including the newly Â logged Â - Â forest, older Â logged Â - Â over forestsÂ Â (treated and untreated),Â Â and un-logged-forestÂ Â Â patches.Â Â TheÂ study began in 1991, and nineteen Â of Â 0.25 Â ha plotsÂ Â were set up in a total Â of Â six blocks Â designatedÂ Â as consecutively Â A, B, C, D, E and F. Â Block A was a newly loggedÂ Â forest and had five plots, Â and Block Â B - Â D were in forest whichÂ had been logged Â in 1979. Â Block B (five plots) had received no silviculturalÂ Â treatment, Â while Block Â C (five plots) and Â D (one plot)Â Â hadÂ beenÂ lightlyÂ Â thinned Â after Â felling and Â further Â Block C received Â a further Â thinning treatmentÂ Â Block Â E (one plot) Â had been Â heavilyÂ Â thinned, Â and Block F (2 plots)Â Â was an un-loggedÂ Â control. TheÂ densityÂ of Â seedling Â varied within Â the study sites, and averaged Â from Â 47,000 ha